Exposure of Pedicle Screws due to Chronic Vertebral Erosion by Tracheostomy Tube Cuff Balloon: A Case Report. Issue 3 (12th July 2022) - Gupta, Arjun; Harbison, R. Alex; Sponseller, Paul D.
Abstract : Case: We report a patient with permanent tracheostomy in the context of muscular dystrophy presented for pneumonia. On bronchoscopy, a pedicle screw was seen penetrating the trachea. Computed tomography revealed significant anterior erosion of the T1-T3 vertebrae due to chronic pressure injury from the tracheostomy cuff, exposing pedicle screws implanted >10 years earlier. The patient was fitted for a custom low-pressure cuff. No further sequelae developed for 4 months. Conclusion: To the best of our knowledge, this is the first case of exposed spinal fusion instrumentation due to chronic vertebral erosion. Early sagittal imaging and the use of low-pressure cuffs may help prevent this complication.